Dark matter and dark energy denote the gravitation of the expanding universe - Annila, Arto; Wikström, Mårten (Frontiers in Physics, 2022)
We reason that it is the gravitation of all ordinary matter, extending from the dense distant past to the sparse present, rather than dark matter, that shows up in galaxy rotation and velocity dispersion. Likewise, we argue that it is this gradient in the gravitational energy due to the expansion, rather than dark energy, that explains Type 1a supernovae brightness vs. redshift data. Our conclusions follow from statistical mechanics, the thermodynamic theory based on the atomistic axiom that everything comprises quanta. In line with the Einstein field equations, the vacuum quanta embodying gravitation, geometrized as spacetime, equate in dynamic balance to the quanta embodying the substance of the stress-energy tensor. In accord with quantum field theory, the proposed ground-state field of paired light quanta complies with Bose-Einstein statistics and assumes an excited state around a particle.